PENGARUH KETERAMPILAN MENGAJAR GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA PGRI PEKANBARU - Arsy Makiini; Syakdanur Nas; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research to analyze the influence of teacher teaching skills and learning motivation on learning outcomes on economic lesson learning subjects in class XI IPS in SMA PGRI Pekanbaru. The sample of this study used saturated samples, or a census of 65 students in the XI IPS class of SMA PGRI Pekanbaru. Data collection in this study used questionnaire and documentation instrument. data was analyzed using multiple regression analysis. The results showed that teacher teaching skills and learning motivation have a significant effect on the learning outcomes. Judging from the value (Rsquare) obtained a value of 0,587. These results prove that the meaning of the influence of teacher theaching skills and learning motivation on learning outcomes is 58,7%. While the remaining 41,3% is influenced by other variables outside this research.Keywods : Teacher teaching skills, learning motivation, learning outcomes